Comparative analysis of shooting consistency among archers of different skill levels - Zhang, B.; Lin, Z.-C. (Quality in Sport, 2025)
Purpose: This study aimed to investigate the biomechanical and electromyographic factors underlying shooting consistency among archers of different skill levels, providing insights into performance optimization and training strategies.